2015
DOI: 10.1590/1982-0216201516013
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida relacionada à voz e à deglutição, a curto prazo, em pacientes submetidos à radioiodoterapia por carcinoma diferenciado de tireoide

Abstract: Qualidade de vida relacionada à voz e à deglutição, a curto prazo, em pacientes submetidos à radioiodoterapia por carcinoma diferenciado de tireoide José Ribamar do Nascimento Junior (1) , Elisabete Carrara-de Angelis (2) , Eduardo Nóbrega Pereira Lima (3)Instituto de Gerenciamento em deglutição -IGD São Paulo, SP, Brasil.Departamento de Fonoaudiologia do Hospital AC Camargo São Paulo, SP, Brasil.Departamento de Medicina Nuclear do Hospital AC Camargo, São Paulo, SP, Brasil. Conflict of interest: non-existentT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The statistically significant difference found in this study between the "physical" and "total" MDADI domains is in line with a Brazilian study carried out with patients with thyroid carcinoma, which found an improvement in the scores of all MDADI domains after three months of treatment with radioiodine therapy (26) . Although the treatment method was different from the treatment of the participants in this study, the difference between the scores of the domains in both studies strengthens the hypothesis that both thyroidectomy and radioiodine therapy can improve the quality of life related to swallowing in patients with thyroid disorders.…”
Section: Discussionsupporting
confidence: 91%
“…The statistically significant difference found in this study between the "physical" and "total" MDADI domains is in line with a Brazilian study carried out with patients with thyroid carcinoma, which found an improvement in the scores of all MDADI domains after three months of treatment with radioiodine therapy (26) . Although the treatment method was different from the treatment of the participants in this study, the difference between the scores of the domains in both studies strengthens the hypothesis that both thyroidectomy and radioiodine therapy can improve the quality of life related to swallowing in patients with thyroid disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Sobre a qualidade de vida relacionada à voz, os estudos desta revisão são medidas importantes para serem avaliadas tendo vista a funcionalidade e a qualidade de vida dos pacientes com ccp na perspectiva de promover a comunicação com os adoecidos pelo CCP. A qualidade de vida relacionada a voz foi identificada como sendo maior em pacientes com câncer de tireóide anteriomente submetidos a iodoterapia, porém os impactos do tratamento se mantiveram discretos em 99% dos pacientes e os que estavam em nível grave passaram ao nível moderado (NASCIMENTO JUNIOR, et al, 2015).…”
Section: A22unclassified